Rancang Bangun Sistem Informasi E-Gudang Pada PT.XYZ Berbasis Website Dengan Framework Laravel - Umam Ma'sum; Diah Rahmawati; Siti Muryanah (JURNAL ILMIAH FAKULTAS TEKNIK, 2023)
This research aims to develop a web-based e-warehouse system for PT. XYZ, a national private company engaged in the printing and packaging industry. Currently, the company still employs conventional methods for data processing, leading to file accumulation and difficulties in accessing archived data. Drawing from previous studies on similar issues in other companies, the author will construct a web-based system using the Laravel framework and Agile methodology to expedite software development. The system aims to facilitate the management and control of raw material inventory, as well as streamline processes related to incoming and outgoing goods and inventory requests. The research employs a quantitative method with observation, interviews, and literature review as approaches. The results demonstrate that the web-based system enhances efficiency in accessing and processing warehouse data in real-time, minimizing stock calculation errors, and presenting warehouse information effectively through an intuitive and informative interface.